Factors associated with climate change worry in older adults: a multidimensional health perspective - Onal, Birol; Kocaman, Ayse Abit; Onal, Seyma Nur (Bmc, 2026)
Background Climate change worry is increasingly recognized as a significant psychological response to environmental threats; however, research in older adults has largely focused on climate-related anxiety or isolated health outcomes. Studies examining climate change worry from a multidimensional health perspective are limited, particularly among older adults living in communities. This study aimed to investigate the relationships between climate change worry and multidimensional health characteristics in older adults. Methods A cross-sectional study included 148 community-dwelling older adults in Turkiye. Participants were assessed using the Climate Change Worry Scale, Standardized Mini Mental State Examination (SMMSE), Athens Insomnia Scale (AIS), World Health Organization Well-Being Index (WHO-5), Geriatric Depression Scale-15 items (GDS-15), and International Physical Activity Questionnaire-Short Form (IPAQ-SF). Multiple linear regression analyses were performed to examine factors associated with climate change worry. Results The overall regression model was statistically significant (R & sup2; = 0.221, F (9,138) = 4.36, p < 0.001). Higher AIS scores (beta = 0.279, p = 0.004), higher education level (beta = 0.193, p = 0.027), and living in urban areas (beta =-0.173, p = 0.039) were significantly associated with greater climate change worry. Age was negatively associated with climate change worry (beta =-0.164, p = 0.044), indicating lower worry in older participants. SMMSE, WHO-5, GDS-15, IPAQ-SF, and sex were not significantly associated with climate change worry in the present model. Conclusions Among community-dwelling older adults, climate change worry was associated with specific sociodemographic and lifestyle-related factors, including sleep quality, educational level, urban residence, and age. In the present model, cognitive status, general well-being, depressive symptoms, and physical activity were not significantly associated with climate change worry. These findings support the need for further research on climate-related concern in later life, particularly in relation to contextual factors.
Keywords: Climate Change Worry; Older Adults; Urban-Rural Residence; Sleep Quality; Education